Economic benefits of animal pollination to Indian agriculture - CHAUDHARY, O P; CHAND, RAMESH (The Indian Journal of Agricultural Sciences, 2017)
In an effort to estimate contribution of animal pollinators toward Indian agriculture, 211 crops (190 crops and 21 commodities) were analyzed using primary data. Production of 108 (51.2%) crops is dependent on animal pollination, 59 (28.0%) did not rely on it and for 44 (20.9%) information is not available. Among 108 crops, pollinator dependence was essential for 14 crops (6.6%, in absence 90-100% reduction in production occurs), great for 34 (16.1%), moderate for 29 (13.7%) and little for 31 (14.7%) crops. Rapeseed and mustard is the most pollinator dependent crop with an estimated economic value of pollination (EVP) of ₹19355.70 crores. Cotton, apple, citrus, guava, tomato, brinjal, chillies, okra, cumin, coriander, soybean are few of a large numbers of crops benefitted hugely by pollinators. Oilseeds greatly depend on insect pollination with 34.07% contribution to yield and resultant economic value of pollination (EVP) is estimated at ₹43993.08 crores from their total economic value (EV) of ₹ 129030.05 crores. Fruits follow with 14.82% (₹17095.45 crores) economic value mostly for 12 major fruits. Value of pollination from vegetables is ₹19498.20 crores (11.10%), fibers (mainly cotton) ₹17290.66 crores (23.39%) and condiments and spices at ₹10109.43 crores (25.47%). Huge research and information gap exists for these crops in India. Of the total value of Indian agriculture (₹ 291369.63 crores at 2012-13 prices or USD 258.27 billion), proportion of animal pollinated crops is ₹ 422827.52 crores ( 84.57 billion), representing 32.74%. Direct contribution of insect pollination to Indian agriculture is staggering ₹112615.73 crores (USD 22.52 billion) annually, representing 8.72%, besides spill over benefits of increase in quality traits, seed production, breeding efficiency, etc. For stagnant Indian agriculture, this “micro concept” of using honey bees for planned pollination of crops has the potential “macro-economic” impact.